‘End of the Goddamned thing!!’ - Richard Williams (Sillages Critiques)
The mystery fiction writer Erle Stanley Gardner and his publisher Thayer Hobson of Morrow devised an unusual procedure for connecting the first ten Perry Mason novels with ‘leads’ to provoke the reader’s curiosity, and so promote the sale of the succeeding book. The genesis of these ‘leads’, and the contrasting views of author and publisher on the requirements of endings in mysteries, is documented through their correspondence. The paper examines Erle Stanley Gardner’s resourcefulness in triggering different types of curiosity, and the issues that could arise when publishers substituted or curtailed these ‘leads’ in reprint editions. In translated editions the endings of these books became especially liable to modifications according to the expectations of the target culture. Differing conventions and fashions for the concluding textual threshold are exemplified from the manuscript evidence (including novels written by Erle Stanley Gardner under the pseudonym A.A. Fair) and from the very extensive dissemination of these best-selling works in book form.